FAO/Bioversity Multi-Crop Passport Descriptors V.2 [MCPD V.2] - June 2012 - Alercia, A.; Diulgheroff, S.; Mackay, M. (Bioversity International, 2012)
The FAO/Bioversity Multi-Crop Passport Descriptors (MCPD V.2) is the result of a thorough revision of the publication originally released by FAO/IPGRI in 2001, which has been widely used as the international standard to facilitate germplasm passport information exchange. In this improved version, the 2001 list of descriptors has been expanded to accommodate emerging documentation needs, derived inter alia from the entry into force of the International Treaty on Plant Genetic Resources for Food and Agriculture and its Multilateral System for access and benefit-sharing, and from technological changes such as the broader use of GPS tools.